Accelerated solvent extraction by using an 'in-line' clean-up approach for multiresidue analysis of pesticides in organic honey. Issue 5 (4th May 2017) - Chiesa, Luca Maria; Labella, Giuseppe Federico; Panseri, Sara; Britti, Domenico; Galbiati, Fabrizio; Villa, Roberto; Arioli, Francesco
ABSTRACT: The worldwide loss of honeybee colonies may be due to their exposure to several contaminants (i.e., pesticides); such contamination may also have impacts on consumers' health. Therefore, it is essential to develop quick and new methods to detect several pesticide residues in honey samples. In this study, the effectiveness of accelerated solvent extraction (ASE) was compared with QuEChERS methods for the analysis of 53 pesticides in organic honey by gas chromatography-triple quadrupole mass spectrometry. Two simple and rapid ASE methods with 'in-line' clean-up were optimised and then compared with QuEChERS. Hexane–ethyl acetate (Hex:EtAc) and Florisil were chosen as extraction solvent and retainer for the first ASE method respectively; acetonitrile and a primary–secondary amine phase (ACN-PSA) were selected for the second ASE method. The methods were validated according to the European Union SANTE/11945/2015 guidelines. The validation parameters showed that QuEChERS and ASE with PSA as retainer had better repeatability than ASE with Hex:EtAc and Florisil. In particular, QuEChERS and ASE (ACN-PSA) showed good recovery, according to the SANTE criteria, for the majority of investigated pesticides. Conversely, when ASE with Hex:EtAc and Florisil was used as the retainer, several compounds showed recoveries lower than the acceptable value of 70%. The ASE in-line method was finally applied to evaluate pesticide concentration in organic honey samples. GRAPHICAL ABSTRACT: